Stroke-Like Neurological Manifestations in Hypertensive Emergency: Diagnostic Challenges and Clinical Lessons from a Case Report - Thaer J. Aljanabi (SHIFAA, 2026)
Neurologic manifestations in patients with hypertensive emergencies are often stroke-like, and rapid recognition of acute cerebrovascular insults or reversible hypertensive neurologic dysfunction with its implications for clinical management and prognosis continue to pose a great challenge in the field of emergency medicine. Although tremendous progress has been made in the use of neuroimaging, normal initial brain computed tomography (CT) does not rule out diagnostic uncertainty, especially in patients with transient neurological symptoms. The diagnostic difficulty of a stroke-like presentation during a hypertensive emergency is discussed in the context of a representative clinical case and incorporates current evidence on the differential diagnoses, emergency evaluation, neuroimagining protocol, therapeutic management and potential pathophysiological mechanisms. The presented case was a 42-year-old man with uncontrolled hypertension and diabetes mellitus who presented with sudden onset of headache, transient numbness and weakness with marked hypertension (181/110 mmHg). Emergency evaluation, which included a non-contrast brain computed tomography (CT) scan, did not show evidence of acute intracranial hemorrhage, and rapid antihypertensive treatment led to resolution of symptoms and discharge the same day. This is a clinical study with a contemporary evidence-based review that has identified limitations of using early neuroimaging, the importance of structured differential diagnosis, and suggested mechanism(s) for reversible neurological dysfunction in hypertensive emergency. This confirms the importance of timely control of blood pressure, thorough neurological evaluation, and clinical discretion to ensure the best possible outcomes and to avoid misdiagnosis in the emergency setting.